Cetuximab‐radiotherapy combination in the management of locally advanced cutaneous squamous cell carcinoma. Issue 2 (14th December 2018) - Joseph, Kurian; Alkaabi, Khalifa; Warkentin, Heather; Ghosh, Sunita; Jha, Naresh; Smylie, Michael; Walker, John
Abstract: Introduction: We report the outcomes of using a combination of cetuximab with radiation therapy (Cetux‐RT) to treat a selected group of patients with locally advanced (unresectable) cutaneous squamous cell carcinoma (LA‐cSCC). This study presents two‐year efficacy and safety data for 8 patients with LA‐cSCC treated within a single institution. Methods: Between 2014 and 2017 a total of eight patients (seven males, one female) with LA‐cSCC received curative intent treatment with Cetux‐RT. All patients received an initial loading dose of cetuximab at 400 mg/m 2 seven days prior to radiotherapy, followed by weekly treatment with 250 mg/m 2, continuing through the end of radiotherapy. Radiation doses were 6600 cGy/30 fr ( n = 2), 6300 cGy/30fr ( n = 2) and 5500 cGy/22 fr ( n = 4). Results: The median age was 81 years (range, 55–87). The ECOG performance status of all patients was between 0 and 2. With a median duration of follow‐up of 25 months (range 10–48 months), five patients remain in a complete response. After a partial response, another patient has relapsed and is receiving palliative chemotherapy, while two patients have died during the period of follow up (one of whom died following progression of disease, the other of an unrelated cause). Treatment in this group of patients was well tolerated, with most toxicities ≤ grade 2, and no toxicities of grade 4/5 reported. Conclusions: Cetux‐RT was well tolerated and provided durable disease control within this patient sample. Our data support the use of the Cetux‐RT regimen for selected patients with inoperable LA‐cSCC and adequate performance status.